Canagliflozin on top of dual renin-angiotensin system blockade in a woman with partial acquired lipodystrophy, type 2 diabetes and severely proteinuric chronic kidney disease: a case report - Biancalana, Edoardo; Ceccarini, Giovanni; Magno, Silvia; Ortenzi, Valerio; Giannese, Domenico; Santini, Ferruccio; Solini, Anna (Frontiers in Endocrinology, 2023)
Sodium glucose cotransporter 2 inhibitors have proven strong efficacy in reducing end-stage renal disease in patients with type 2 diabetes. We are presenting here the case of a 40-year-old woman with acquired partial lipodystrophy, type 2 diabetes and essential hypertension complicated by chronic kidney disease and proteinuria in the nephrotic range. She first came to our attention in 2012; estimated glomerular filtration rate (eGFR) was 41.5 ml/min/1.73 m2 and total proteinuria was 375 mg/24h; she was treated with dual renin angiotensin system blocking. Proteinuria significantly increased during the following years, reaching a nephrotic range (>5 g/day). A kidney biopsy revealed a tubule-interstitial involvement compatible with type 2 diabetes. Leptin replacement therapy, started in 2018, improved glycaemic control and lipid profile, also determining a reduction in insulin total daily dose. In 2019, after the publication of the CREDENCE study, canagliflozin was started on top of losartan and ramipril. After an initial, expected eGFR drop, kidney function stabilized, and albuminuria significantly reduced (from 4120 to 984 mg/24h), while serum potassium showed only minimal increase. At last follow-up (2022) total proteinuria was still reducing (510 mg/24h), while kidney function was substantially unchanged (eGFR 40 ml/min/1.73 m2). This case report suggests that, despite not recommended in international guidelines, the use of SGLT2i in combination with dual renin angiotensin system blockade should be considered in specific conditions and under close clinical monitoring.